2022
DOI: 10.48550/arxiv.2205.07694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Everywhere regularity results for a polyconvex functional in finite elasticity

Abstract: Here we develop a regularity theory for a polyconvex functional in 2 × 2−dimensional compressible finite elasticity. In particular, we consider energy minimizers/stationary points of the functionalwhere Ω ⊂ R 2 is open and bounded, u ∈ W 1,2 (Ω, R 2 ) and ρ : R → R + 0 smooth and convex with ρ(s) = 0 for all s ≤ 0 and ρ becomes affine when s exceeds some value s0 > 0. Additionally, we may impose boundary conditions.The first result we show is that every stationary point needs to be locally Hölder-continuous. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…By the higher-order regularity result [17,Thm 1.4] we know that u = re M R ∈ W 2,2 (B, R 2 ) and d ∈ C 1 ([0, 1]), is enough to imply full local smoothness u = re M R ∈ C ∞ loc (B, R 2 ) which guarantees smoothness at the origin, the smoothness can then be extended by limit taking of r, d and their derivatives up to the harmless boundary at R = 1, showing the claim. Now for the second part of the statement we first note that ρ(d) > 0 for all d > 0 implies that there exists a δ > 0 s.t.…”
Section: 3mentioning
confidence: 93%
See 1 more Smart Citation
“…By the higher-order regularity result [17,Thm 1.4] we know that u = re M R ∈ W 2,2 (B, R 2 ) and d ∈ C 1 ([0, 1]), is enough to imply full local smoothness u = re M R ∈ C ∞ loc (B, R 2 ) which guarantees smoothness at the origin, the smoothness can then be extended by limit taking of r, d and their derivatives up to the harmless boundary at R = 1, showing the claim. Now for the second part of the statement we first note that ρ(d) > 0 for all d > 0 implies that there exists a δ > 0 s.t.…”
Section: 3mentioning
confidence: 93%
“…), but not necessarily any better, and r(0 What does the literature tell us about the regularity of stationary points/minimizers of the energy I? This functional has recently been introduced in [17]. There it is shown that for arbitrary γ ∈ (0, ∞) any stationary point of the energy I subject to arbitrary L 2 − boundary data needs to be locally Hölder-continuous and a higher-order regularity result is obtained.…”
Section: Introductionmentioning
confidence: 99%